PERTANGGUNGJAWABAN PELAKU PENYANDANG RETARDASI MENTAL DALAM KASUS PENCABULAN ANAK DALAM STUDI KOMPARATIF HUKUM ISLAM DAN HUKUM PIDANA - Hardi Done; Trimurti Jayantoro (Jurnal Ilmu Hukum Kanturuna Wolio, 2023)
This study aims to look at the accountability of perpetrators with mental retardation in cases of child molestation in a comparative study of Islamic law and criminal law. The research method used in normative legal research is by examining literature. The approach used by the author in this study uses a case approach and laws and text rules. The data method is used by collecting the materials needed in a study that can be done by means of a literature study (literature research). The data analysis method used a qualitative analysis method using a normative juridical approach, namely seeing law as a norm in society and using a comparative study of Islamic law and criminal law. Referring to this research method, the accountability of perpetrators of mental retardation in cases of child molestation, both according to criminal law and Islamic criminal law, agrees that they can still be held accountable for mild mental retardation, but severe mental retardation cannot be held accountable.